Efektivitas Model Pembelajaran Kontekstual Terhadap Pemahaman Konsep Matematika Siswa Sekolah Dasar - Ika Nadia Putri; Meli Ramadhani; Dina Musarofah; Khodijah; Selvi Melani; Muhammad Fahmi Usman; Mansur (PT. Hasba Edukasi Mandiri, 2026)
This study aims to determine the effectiveness of the contextual learning model on elementary school students' understanding of mathematical concepts. Students' poor understanding of mathematical concepts is often caused by a teacher-centered learning process that lacks connection to real-life situations. The contextual learning model is seen as an alternative that can help students understand mathematical concepts through direct experiences and situations close to everyday life. Thus, the contextual learning model is effective in improving elementary school students' understanding of mathematical concepts and can be used as an alternative learning model by teachers in the mathematics learning process.